Cytological features of basal cell adenocarcinoma of the salivary glands. Issue 7 (22nd March 2019) - Ishida, Mitsuaki; Okano, Kimiaki; Sandoh, Kaori; Ebisu, Yusuke; Fujisawa, Takuo; Iwai, Hiroshi; Tsuta, Koji
Abstract : The cytological features of basal cell adenocarcinoma (BAC) of the salivary gland, a rare carcinoma, have not been well described. This study included patients who were histopathologically diagnosed with BAC and who underwent preoperative fine‐needle aspiration cytological examination. Cytological characteristics, including background, arrangement and shape of the neoplastic cells, nuclear and cytoplasmic features, and presence of stromal spindle cells, were reviewed. Seven patients were enrolled in the study. The cytological specimens were cellular and composed of large or small clusters with occasional discohesive neoplastic cells at the periphery. The predominant cellular morphology was spindle‐shaped in four cases, and small round‐shaped in three cases. These neoplastic cells were tightly packed, showed high cellularity and overlapping nuclei, and had mildly to moderately enlarged round to oval nuclei with occasional small nucleoli and scant cytoplasm. Stromal spindle cells were observed around the basaloid cells in three cases (42.9%). All histology‐proven stromal spindle cell‐positive cases had stromal spindle cells in the cytological specimens. The study findings clearly demonstrate the relatively high frequency of stromal spindle cells in cytological specimens of BAC. This finding is characteristic of BAC, although basal cell adenoma of salivary gland frequently has stromal spindle cells in the cytological specimens. The characteristic that differentiates BAC from basal cell adenoma is the presence of tightly packed and high cellular clusters with discohesive neoplastic cells. An understanding of these cytological features can aid the cytodiagnosis of BAC.